Panel Data Analysis of Investment Decisions and Firm Value in the Indonesian Consumer Goods Industry - Wulandari, Wulandari (Yayasan Pendidikan Penelitian Pengabdian Al-amsi, 2025)
This study aims to analyze the influence of business risk, investment decisions, and good corporate governance on firm value. The research was conducted using secondary data derived from financial statements of food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The independent variables are business risk, investment decisions, managerial ownership, institutional ownership, and independent commissioners, while firm value serves as the dependent variable. Panel data regression is employed using EViews 12. The study finds that only investment decisions have a statistically significant and positive effect on firm value, aligning with signaling theory.